Implikasi Pengelolaan Kawasan Aglomerasi dalam Undang-Undang Daerah Khusus Jakarta terhadap Pelaksanaan Desentralisasi dan Otonomi Daerah - Yusuf, Rizki Fauzan; Hidayat, Syarif; Rohman, Azmi Fathu; Rizqiyanto, Naufal; Yusuf, Muhammad Rifai (UIN Sunan Kalijaga Yogyakarta, 2024)
For more than two decades, the concept of agglomeration has been applied in DKI Jakarta, beginning with Law No. 34 of 1999 and continuing with Law No. 29 of 2007 as its legal foundation. With the government's execution of the plan to relocate the national capital from Jakarta to East Kalimantan, Law No. 2 of 2024 emerged as the legal policy framework for adjusting DKI Jakarta’s status. One of the key regulatory innovations introduced in this new law is the establishment of the Agglomeration Area Council, tasked with coordinating and evaluating spatial planning and development plans within the agglomeration area. While this structure presents positive potential for the governance of Jakarta and its surrounding regions, the agglomeration area arrangement under the new law signals a centralistic tendency—evident, for instance, in the President’s direct involvement in determining the membership of the Agglomeration Area Council. This may conflict with the principles of decentralized governance. This study employs normative legal research using a statutory approach to examine relevant legislation, particularly the provisions in the DKJ Law, and a conceptual approach to explain the general features of agglomeration areas. The findings indicate, first, that the agglomeration concept regulated by the DKJ Law is centralized, with the central government playing a dominant role, contrasting with agglomeration practices in other regions that are more decentralized. Second, the implications for the implementation of autonomy in DKJ are negative, as the central government's dominant role limits the flexibility of DKJ’s local government in decision-making and may lead to DKJ’s dominance over neighboring areas within the agglomeration zone. On the positive side, the surrounding regions benefit from the central government's support, indicating that the asymmetric design of DKJ governance also positively affects neighboring regions within the agglomeration area. Abstrak: Lebih dari dua dekade konsep aglomerasi diterapkan di DKI Jakarta, dimulai dengan UU No. 34 Tahun 1999 hingga UU No. 29 Tahun 2007 sebagai landasan yuridisnya. Seiring eksekusi rencana pemindahan Ibu Kota Negara oleh pemerintah dari Jakarta ke Kalimantan Timur, lahir UU No. 2 Tahun 2024 sebagai politik hukum penyesuaian status DKI Jakarta. Salah satu pembaharuan pengaturan konsep aglomerasi dalam UU terbaru ini adalah hadirnya Dewan Kawasan Aglomerasi yang akan melakukan koordinasi hingga evaluasi penataan ruang dan rencana pembangunan kawasan aglomerasi. Meski berpeluang positif bagi penataan Jakarta dan sekitarnya, struktur pengaturan kawasan aglomerasi DKJ memberikan sinyal sentralistis ditunjukkan salah satunya keterlibatan langsung Presiden dalam penentuan keanggotaan Dewan Kawasan Aglomerasi, hal mana dapat berbenturan dengan penyelenggaraan pemerintahan yang terdesentralisasi. Penelitian yang digunakan dalam tulisan ini adalah penelitian hukum normatif dengan pendekatan perundang-undangan (statutory approach) untuk menelaah peraturan perundang-undangan terkait, khususnya ketentuan dalam UU DKJ dan pendekatan konseptual (conceptual approach) untuk menjelaskan fitur kawasan aglomerasi secara umum. Hasil penelitian menunjukkan pertama, konsep kawasan aglomerasi yang diatur UU DKJ bersifat terpusat/sentralistis dimana peran pemerintah pusat dominan dalam pengelolaannya, hal ini berbeda dengan praktik aglomerasi di beberapa daerah yang justru lebih terdesentralisasi. Kedua, implikasi terhadap pelaksanaan otonomi di DKJ bersifat negatif karena fleksibilitas pemerintah DKJ terbatas dalam pengambilan keputusan akibat peran pemerintah pusat yang besar serta kemungkinan dominasi DKJ terhadap daerah sekitar dalam cakupan kawasan aglomerasi. Efek positifnya adalah terbantunya daerah sekitar DKJ karena turut memperoleh sokongan dari pemerintah pusat sehingga tampak desain asimetrisme DKJ dirasakan pula oleh daerah sekitar dalam kawasan